Comparison of laser Doppler and laser speckle contrast imaging using a concurrent processing system - Sun, Shen; Hayes-Gill, Barrie R.; He, Diwei; Zhu, Yiqun; Huynh, Nam T.; Morgan, Stephen P. (Elsevier, 2016)
Full field laser Doppler imaging (LDI) and single exposure laser speckle contrast imaging (LSCI) are directly compared using a novel instrument which can concurrently image blood flow using both LDI and LSCI signal processing. Incorporating a commercial CMOS camera chip and a field programmable gate array (FPGA) the flow images of LDI and the contrast maps of LSCI are simultaneously processed by utilizing the same detected optical signals. The comparison was carried out by imaging a rotating diffuser. LDI has a linear response to the velocity. In contrast, LSCI is exposure time dependent and does not provide a linear response in the presence of static speckle. It is also demonstrated that the relationship between LDI and LSCI can be related through a power law which depends on the exposure time of LSCI.